2008
DOI: 10.1063/1.3033552
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of buckling-induced plasticity

Abstract: Molecular dynamics simulations of thin film buckling demonstrate that high compressive stresses are localized in the straight-sided wrinkle leading to the nucleation of dislocations, which are mobile and plastically release a large amount of the strain. As a consequence, the maximum deflection determined in the framework of elasticity theory is found to be overestimated. Finally, the resulting plastic deformation has been estimated and included in the expression of the deflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The observation of circular buckles at large scales is thus a relevant marker of the occurrence of plastic events in the films. Such plastic events have been evidenced by molecular dynamic simulations (Durinck et al, 2008;Ruffini et al, 2013) and are characterized by a modified maximum deflection of buckles (as compared to a pure elastic response), in good agreement with experimental investigations on ductile films (Colin et al, 2009;Colin et al, 2007). Moreover, the combined effect of plastic events with a pressure mismatch mentioned previously (between the external and internal parts of the buckles) may now explain the formation of donut-and croissant-like structures (Hamade et al, 2015), experimentally observed on gold films in Fig.…”
Section: Donut-and Croissant-like Structure As Markers Of Both Pressu...supporting
confidence: 88%
“…The observation of circular buckles at large scales is thus a relevant marker of the occurrence of plastic events in the films. Such plastic events have been evidenced by molecular dynamic simulations (Durinck et al, 2008;Ruffini et al, 2013) and are characterized by a modified maximum deflection of buckles (as compared to a pure elastic response), in good agreement with experimental investigations on ductile films (Colin et al, 2009;Colin et al, 2007). Moreover, the combined effect of plastic events with a pressure mismatch mentioned previously (between the external and internal parts of the buckles) may now explain the formation of donut-and croissant-like structures (Hamade et al, 2015), experimentally observed on gold films in Fig.…”
Section: Donut-and Croissant-like Structure As Markers Of Both Pressu...supporting
confidence: 88%
“…A likely mechanism is the nucleation and/or evolution of dislocations at the compressed side of the silicon beam, 16 which can lead to a significant reduction in the deflection of buckled beams. 17 These irreversible processes result in a reduction of the flight distance to a stable value. Using a high-resolution optical microscope, we qualitatively observed changes in the beam shape before and after repetitive switching.…”
Section: ͪ ͑2͒mentioning
confidence: 99%
“…This method has been successfully used to resolve some problems related to vibration, bending and buckling stability of nanobeam [16]. However, post-buckling deformation of nanobeam is still unclear, and of great study interest in recent years [17][18][19][20]. Compared with stability, post-buckling deformation of nanobeam is much more difficult to be predicted [21].…”
Section: Introductionmentioning
confidence: 99%